Analisis Total Quality Management dalam Memperbaiki Kualitas Produk pada Perusahaan Garmen (Studi Kasus pada CV Sakti Abadi Garmindo di Wonogiri) - Francisca Audry Kournikova; Erni Widajanti; Sutarno (Teewan Journal Solutions, 2026)
Product quality is key to attracting consumers; therefore, it is a crucial concern for companies, given the competitiveness of companies producing similar or similar products. All companies have specific standards for determining product quality, including CV Sakti Abadi Garmindo, a garment company. The purpose of this study was to analyze Total Quality Management and its constraints in improving the quality of defective products in the garment production process at CV Sakti Abadi Garmindo in Wonogiri. This study used a qualitative method through interviews with the Owner, production Leader, and quality control staff. The hypothesis of this study states that the implementation of Total Quality Management (TQM) at CV Abadi Garmindo is suboptimal. Inadequate training, a lack of quality planning, and a lack of professional development for employees are obstacles to TQM analysis in improving the quality of defective products in garment production at CV Sakti Abadi Garmindo in Wonogiri. Based on the interviews, it was revealed that TQM implementation is not comprehensive and systematic. This is due to the lack of adequate training for employees, the lack of structured quality planning, and the minimal use of professional development and technology. Therefore, the results of this study indicate that both hypotheses are proven true.